Longitudinal Interactional Histories Bilingual and Biliterate Journeys of Mexican Immigrant-origin Youth - Kibler, Amanda K. (Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This book explores the lives of five Mexican immigrant-origin youths in the United States, documenting their language and literacy journeys over an eight-year period from adolescence to young adulthood. In these qualitative case studies, the author uses a "longitudinal interactional histories approach" (LIHA) to explore literacy events in which the young people participated over time, telling the stories behind texts they created in order to better understand opportunities for bilingual and biliterate development available inside and outside of formal schooling. The book begins with an overview and exploration of theories and research underpinning the project, with a focus on countering minoritizing discourses faced by many multilingual immigrant youth and prioritizing the "goodness" of their experiences. The study's methodology, including LIHA, is presented, before individual case studies of all five youth are explored. The book closes with a synthesis of these cases and exploration of pedagogical, policy, and research implications. It will be of particular interest to students and scholars of education, applied linguistics and sociolinguistics, as well as teachers and policy-makers working with bilingual and biliterate immigrant youth. Amanda Kibler is an Associate Professor in the College of Education at Oregon State University, USA. Her work focuses on better understanding the language and literacy development of multilingual children and adolescents from immigrant backgrounds and using these insights to support educators in providing more equitable learning opportunities for all students.